2003
DOI: 10.1111/1467-8276.00108
|View full text |Cite
|
Sign up to set email alerts
|

Diseconomies of Size with Fixed Managerial Ability

Abstract: Managerial ability has important implications for farm growth. In this article we first show in a production model that increasing output with a fixed level of managerial ability can lead to a decrease in profits. Next, we discuss the effect that managerial ability has on economies of size. In the empirical part, economies of size are estimated for a sample of dairy farms using a proxy for managerial ability, which is calculated as a technical efficiency index. The results show that increasing farm size while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…Fifth, managerial capability in agriculture may be a lumpy input, which in turn Fifth, managerial capability in agriculture may be a lumpy input, which in turn limits scale economies and the potential for farm growth (Tolley 1970; Alvarez and limits scale economies and the potential for farm growth (Tolley 1970;Alvarez and Arias 2003). In Sumner and Leiby (1987), we showed that human capital of operaArias 2003).…”
Section: What Drives Differences In Farm Size and Shifts In Farm Sizementioning
confidence: 83%
“…Fifth, managerial capability in agriculture may be a lumpy input, which in turn Fifth, managerial capability in agriculture may be a lumpy input, which in turn limits scale economies and the potential for farm growth (Tolley 1970; Alvarez and limits scale economies and the potential for farm growth (Tolley 1970;Alvarez and Arias 2003). In Sumner and Leiby (1987), we showed that human capital of operaArias 2003).…”
Section: What Drives Differences In Farm Size and Shifts In Farm Sizementioning
confidence: 83%
“…The value of the cost elasticity with respect to output is 1.13 (significantly different from 1), indicating the existence of decreasing returns to scale. Alvarez and Arias (2003) have suggested that the presence of diseconomies of size can be due to farms increasing size while holding their managerial ability constant. Turning to the inefficiency model, both variables are significant.…”
Section: Estimation and Resultsmentioning
confidence: 99%
“…Section 4 contains the empirical model and Section 5 contains a description of the data. In Section 6, we ' Some papers have shown that farmers with low management (technical efficiency) levels have difficulties exploiting economies of size (Hubbard and Dawson, 1987;Alvarez and Arias, 2003). present the econometric estimation, and in Section 7, we discuss some conclusions.…”
Section: Introductionmentioning
confidence: 99%